Design and Manufacture of Child Prosthesis for Higher Members Below the Elbow Through Reverse Engineering - E. Pozo; E. Medina; A. Pazmiño (ESPOCH Congresses, 2021)
Abstract The objective was to build a prosthesis with its elements such as socket, forearm and hand. The prostheses that are below the elbow generated the motivation for the investigation, being an important factor the correct adaptation of the socket to the stump in a personalized way creating an adjustment due to the vacuum that is generated between these elements, without the need to use a harness. For the design and construction of the prosthesis prototype, a Kinect device was used to obtain a point cloud of the geometric model, the alginate for the manufacture of the mold and plaster that is used to obtain the shape of the hand. The result is an individualized prosthesis design built based on the patient's own dimensions and validated using finite elements; with the purpose of making changes and improvements in the design, to have a prosthesis of easy placement and use.